An oral delivery vehicle based on konjac glucomannan acetate targeting the colon for inflammatory bowel disease therapy - Wang, Chuang; Guo, Zhenzhao; Liang, Jialuo; Li, Na; Song, Rijian; Luo, Lei; Ai, Yilong; Li, Xia; Tang, Shunqing (Frontiers in Bioengineering and Biotechnology, 2022)
Orally administered colon-targeted delivery vehicles are of major importance in the treatment of inflammatory bowel disease (IBD). However, it remains a challenge to maintain the integrity of such delivery vehicles during treatment, particularly in the gastric environment, which may cause untimely drug release before reaching the targeted colon. Herein, an oral colon-targeted drug delivery system (OCDDS) based on acetylated konjac glucomannan (AceKGM) has been developed in this work, which accomplishes colonic localization release and targets local inflammatory macrophages. The AceKGM nanoparticle-loading curcumin (Cur) was successfully fabricated by emulsion solvent evaporation techniques. DLS, AFM, and SEM were used in order to evaluate the nanoparticles’ diameter as well as their in vitro drug release profile, and reactive oxygen species (ROS) scavenging results showed that the OCDDS considerably retained the activity of Cur treated with simulated gastric fluid (SGF) and controllably released in simulated intestinal fluid (SIF). In addition, the adhesion experiment results indicated that the nanoparticle could accumulate on the colonic macrophages. Evaluations in colitis mice showed that the treatment significantly alleviated the symptoms of colitis by decreasing the local level of myeloperoxidase (MPO) and the disease activity index (DAI) score in mice. In summary, the results of our research demonstrate that Cur–AceKGM nanoparticles exhibit significantly improved therapeutic efficacy compared to orally administered free Cur and can be developed as an effective drug delivery vehicle for IBD treatment.